Modeling brand resonance score (BRS) – an application in financial services. (12th February 2018) - Raja Ambedkar, Ande; Murugesan, Punniyamoorthy; Thamaraiselvan, N.
Abstract : Purpose: The experts in industry and academicians value brand resonance is the prerequisite factor in the firms of financial services. In this regard, the purpose of this paper is to model the brand resonance score (BRS) for modified customer-based brand equity (CBBE) model in mutual fund financial services using structural equation modeling (SEM) and analytic network process (ANP). Design/methodology/approach: Criteria and sub-criteria relative weights are calculated from the SEM and sub-sub-criteria relative weights are measured through pair-wise comparison matrix for BRS modeling using ANP approach. Findings: The brand resonance using ANP has been quantified, and BRSs of each brand through brand judgments and brand feelings criteria are calculated using two renowned Indian mutual fund services brands State Bank of India and Hong Kong and Shanghai Banking Corporation. Research limitations/implications: Interdependency between sub-criteria are not explored. This research study is specific to Indian bank mutual fund services context. Practical implications: Research findings provide useful guidelines for fund managers/analysts of mutual fund service firms to improve the brand resonance to investors. Originality/value: The paper explained modeling BRS using ANP technique which helps organizations quantify the brand resonance effectively.